Adaptation of African and Striped Catfish in Peat Water of Low pH - Ardianor Ardianor; Noor Syarifuddin Yusuf; Tutwuri Handayani; Hamdhani Hamdhani (Universitas Gadjah Mada, 2023)
The adaptation of African (Clarias gariepinus) and striped catfish (Pangasianodon hypophthalmus) on peat water with low pH was successfully done. The treated fish were reared on a mixture gradient of peat water and borehole water in the fiber tanks as an adaptation process, with a control treatment of 100% borehole water. After adapting to 100% peat water, catfish were then transferred into the enclosure nets (hapa) and placed on a man-made peat water pond. The mortality, length, weight of catfish, and water quality parameters were recorded and measured. Results showed that subject catfish can be adapted and adapt with peat water of low pH from the fingerling size to adult with small mortality. Fish were acclimatized and gradually adapted after 58 days in the fiber tanks with nearly 100% peat water, and let for the next 38 days. The growth rate of both catfish between the treatment and control tank did not significantly differ. Fish was then moved to the enclosure nets on the ponds after 96 days. This indicates that by adaptation mechanism, catfish can survive and grow in peat water of low pH and possibly be reared in dynamic peat waters (rivers, lakes, and ponds).